2020
DOI: 10.1128/aem.02808-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Required for Glucan Exopolysaccharide Production in Lactobacillus johnsonii Suggests a Novel Biosynthesis Mechanism

Abstract: Lactobacillus johnsonii FI9785 makes two capsular exopolysaccharides-a heteropolysaccharide (EPS2) encoded by the eps operon and a branched glucan homopolysaccharide (EPS1). The homopolysaccharide is synthesized in the absence of sucrose, and there are no typical glucansucrase genes in the genome. Quantitative proteomics was used to compare the wild type to a mutant where EPS production was reduced to attempt to identify proteins associated with EPS1 biosynthesis. A putative bactoprenol glycosyltransferase, FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Lactobacillus johnsonii (Mayer et al, 2020) Glucan will extend to the crumb porosity of bread Improvement of bread texture Limosilactobacillus reuteri (Leemhuis et al, 2014) (Continued) Levilactobacillus brevis (Lyu et al, 2019) Levilactobacillus brevis D17 (Gong et al, 2019) GadC transports L-glutamate into the cell Lactococcus lactis (Small and Waterman, 1998) Glutamate decarboxylase and pyridoxal-5 -phosphate participate in the decarboxylation reaction of L-glutamate Lactococcus lactis (Cui et al, 2020) The cell immobilization technology increase GABA production Levilactobacillus brevis RK03 (Hsueh et al, 2017) Levilactobacillus brevis (Shi et al, 2017) Flavor substances SHMT gene encodes a serine hydroxymethyltransferase with threonine aldolase activity Produce flavor substances (2,3-butanedione and 2,3-pentanedione, etc.) in wine, vinegar, bread, sourdough and cheese…”
Section: Exploration Of a New Way Of Glucan Biosynthesismentioning
confidence: 99%
“…Lactobacillus johnsonii (Mayer et al, 2020) Glucan will extend to the crumb porosity of bread Improvement of bread texture Limosilactobacillus reuteri (Leemhuis et al, 2014) (Continued) Levilactobacillus brevis (Lyu et al, 2019) Levilactobacillus brevis D17 (Gong et al, 2019) GadC transports L-glutamate into the cell Lactococcus lactis (Small and Waterman, 1998) Glutamate decarboxylase and pyridoxal-5 -phosphate participate in the decarboxylation reaction of L-glutamate Lactococcus lactis (Cui et al, 2020) The cell immobilization technology increase GABA production Levilactobacillus brevis RK03 (Hsueh et al, 2017) Levilactobacillus brevis (Shi et al, 2017) Flavor substances SHMT gene encodes a serine hydroxymethyltransferase with threonine aldolase activity Produce flavor substances (2,3-butanedione and 2,3-pentanedione, etc.) in wine, vinegar, bread, sourdough and cheese…”
Section: Exploration Of a New Way Of Glucan Biosynthesismentioning
confidence: 99%
“…3). The BT_1524 gene is predicted to encode an integral membrane protein with a Gtr-A motif (Pfam); other Gtr-A family proteins are involved in cell surface polysaccharide or exopolysaccharide synthesis [25][26][27] .…”
Section: Functional Characterization Of the Inositol Lipid Clustermentioning
confidence: 99%
“…Since PFC may have positive effect on the excretion of UA, it is therefore encouraged to further study whether this is associated with changes in the abundance of Lactobacillus in the gut. The species Lactobacillus_johnsonii_FI9785 and Lactobacillus_animalis are known to have probiotic effects in animals ( Karunasena et al, 2013 ; Mayer et al, 2020 ), and we found that the abundances of these particular species were significantly greater in CKD-P group, which implies that PFC may promote the multiplication of probiotic Lactobacillus species.…”
Section: Discussionmentioning
confidence: 53%